Filogeografía de Elacatinus puncticulatus (Teleostei, Gobiidae) en el Pacífico oriental tropical - Sandoval Huerta, Edgar Raúl (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Geographic barriers to the dispersal of individuals can generate or maintain genetic structure among populations. In the Tropical Eastern Pacific, Central American and Sinaloan gaps, are described as discontinuities responsible for limiting the movement of reef fishes and obstruct the dispersal of pelagic larvae to prevent the establishment. These gaps delimit the continental regionalization of the POT, dividing it into three provinces: Cortez, Mexican and Panamic. However, there are other factors that can act as movement barriers to fishes with semibenthonic characteristics. Oceanographic processes such as currents, gyres and upwelling can promote local retention of pelagic larvae. To identify and determine the efficiency of Ocean- Geographical Barriers, a phylogeographer study of red head goby Elacatinus puncticulatus (Teleostei, Gobiidae) was performed using molecular markers of mitochondrial (mtDNA) and nuclear DNA (nDNA). Were obtained 117 cytochrome b (Cytb) sequences (1140 bp), 37 Control Region (CR) sequences (407 bp), 11 rhodopsin (Rho) gene nuclear sequences (816 bp) and 29 sequences of intron 1 of the gene of the ribosomal protein S7 ( 735 bp). Haplotype diversity indices (Hd), nucleotide diversity (?) and the average nucleotide differences (k), for the total of individuals were significantly greater (Hd=0.959; ?=0.0112; k=12.751) in Cytb to that shown by the sequences of Rho (Hd=0.615; ?=0.0010; k=0.846) and S7 (Hd=0.628; ?=0.0011; k=0.798), being even higher than CR (Hn=0.664; ?=0.0065; k=2.623). The Mexican Province showed higher values of genetic diversity for Cytb and S7, while the Panamic Province was higher values for RC and Rho. By marker, Cytb was the only with Hd higher than 0.5 for the three provinces and for most populations.

Para identificar y determinar la eficiencia de Barreras Oceánico-Geográficas, se realizó́ un estudio filogeográfico del gobio cabeza roja Elacatinus puncticulatus (Teleostei, Gobiidae), mediante marcadores moleculares de ADN mitocondrial (ADNmt) y nuclear (ADNn). Se obtuvieron 117 secuencias de 1140 pb de citocromo b (Cytb), 37 secuencias de la región control (RC) (407 pb), 11 de la rodopsina (Rho) (816 pb) y 29 del intrón 1 del gen de la proteína ribosomal S7 (735 pb). Los índices de diversidad haplotípica (Hd), diversidad nucleotídica (π) y el promedio de diferencias nucleotídicas para el total de individuos fueron notablemente mayores (Hd=0.959; π=0.0112; k=12.751) en Cytb, que para la Rho (Hd=0.615; π=0.0010; k=0.846) y S7 (Hd=0.628; π=0.0011; k=0.798), siendo incluso mayores a los de la RC (Hd=0.664; π=0.0065; k=2.623). La Provincia Mexicana mostró valores mayores de diversidad genética para Cytb y S7, mientras que la Provincia Panámica resultó con mayores valores para la RC y Rho. Por marcador, Cytb fue el único con valores de Hd mayores a 0.5 para las tres provincias y para la mayoría de las poblaciones. La D de Tajima no rechazó el modelo neutral para el total de las secuencias de Cytb (D=-0.674, P=0.278), sin embargo la F de Fu fue significativamente negativa (F=-24.173, P= 0.001). Los resultados del análisis de la distribución de diferencias pareadas, la alta diversidad haplotípica ligada a una baja diversidad nucleotídica y los valores negativos de la F de Fu sugieren una expansión poblacional reciente. Los análisis filogenéticos a través de Neighbor-Joining, Máxima Verosimilitud e Inferencia Bayesiana de Coalescencia, identificaron una división entre las poblaciones de las Provincias de Cortés y Mexicana con respecto de la Provincia Panámica que los separó en dos clados. Además, se identificó́ una subdivisión en la Provincia Panámica que separa a Costa Rica y Panamá́ de Ecuador.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2014-0417; Opción en ecología y conservación; Genética; Barreras; Oceanografía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1702